The effects of organic manure and chemical fertilizer on the growth and nutrient concentrations of yellow poplar (Liriodendron tulipifera Lin.) in a nursery system - Han, Si Ho; An, Ji Young; Hwang, Jaehong; Kim, Se Bin; Park, Byung Bae (Forest Science and Technology, 2016)
Soil nutrient management is necessary to maintain the constant productivity of nursery systems as well as good quality soil. This study investigated the effects of organic manure and chemical fertilizer treatments on growth performance and soil and tissue chemical properties. Two-year-old yellow poplar (Liriodendron tulipifera L.) seedlings were treated with an organic manure (1000 g/m 2 ; mixture of poultry manure, cattle manure, swine manure, and sawdust), nitrogen-phosphorus-potassium (NPK) chemical fertilizer (urea, 30 g/m 2 ; fused superphosphate, 70 g/m 2 ; potassium chloride, 15 g/m 2 ), and organic manure plus NPK chemical fertilizer. Control seedlings were left untreated. Growth of seedlings, soil properties, and nutrient concentrations were measured to compare the treatments. Organic manure significantly increased the soil pH and the concentrations of nitrogen, available phosphorus, exchangeable potassium, calcium, and magnesium. In contrast, the NPK chemical fertilizer decreased the soil pH and exchangeable calcium concentration, did not affect the soil concentrations of nitrogen and magnesium, and increased the concentrations of available phosphorus and exchangeable potassium. Fertilization treatments increased the seedling height and root collar diameter by 21% and 29%, respectively, and the mean dry weight of the stems and leaves by 72% and 123%, respectively; but a synergistic effect of the organic manure and NPK fertilizer was not observed. Compared to the effects of the fertilization treatments on the soil properties, the effects on nutrient concentrations in the leaves, stems, and roots were relatively small. These findings indicate that organic manure derived from livestock byproducts and sawdust can be utilized in seedling production systems.